THE METHOD OF DETERMINING THE DIELECTRIC RELATIVE PERMITTIVITY IN THE MM AND SUBMM WAVELENGTH RANGES BASED ON THE MEASURING OF THE PLASMON-POLARITONE RESONANCE PARAMETERS - Lytvynenko, L. N.; Myshenko, V. V.; Bortsov, V. V.; Lisachenko, V. M.; Polikarpov, O. V.; Gavrikov, V. K.; Spevak, I. S. (Видавничий дім «Академперіодика», 2020)
Purpose: The purpose of the work is to develop a new method for determining the complex dielectric permeability of dielectrics in mm and submm wavelength ranges.Design/methodology/approach: The proposed method consists in registration of parameters of a plasmon polariton resonance, which arises at diffraction of electromagnetic radiation on a diffraction grating created on the surface of the conductive medium (metal or semiconductor) and registration of changes in these parameters when applied to the grating film of the material whose dielectric permeability should be found. On the laboratory unit, created on the basis of the terahertz HCN-laser, the dependence of the intensity of radiation, mirrored reflected from the grids, from the angle of incidence and determined the position and width of the plasmon-polaritone resonance for a clean grid and the same grid covered with the dielectric film. From comparison of these parameters, the values of the resonance shear and widening caused by the presence of the film were found. On the other hand, from the theoretical solution of the mentioned problem of diffraction under the conditions of a plasmon-polaritone resonance, the dependences of the resonance shear and width on optical characteristics of the investigated film (under the conditions of its small optical thickness) were found. Comparison of experimentally found and theoretically defined values of displacement and width of the resonance allows to determine the complex dielectric permeability of the film (at its known thickness).Findings: Test measurements of the complex dielectric permeability of the reference polypropylene film have been made by the proposed method. The measurements have been compared with the known data obtained earlier by spectroscopic and interferometric methods. It was found that the obtained and known values of the actual parts of the polypropylene dielectric permeability differ by less than 10 %, and the values of their imaginary parts coincide in the order of magnitude.Conclusions: The received results testify to suitability of the offered method for operational express measurements of optical characteristics of dielectrics films with small optical thickness.Key words: measurement of optical characteristics, dielectric permeability, terahertz range, electromagnetic radiation diffraction, plasmon polariton resonanceManuscript submitted  22.06.2020Radio phys. radio astron. 2020, 25(3): 231-239REFERENCES1. TYDEX, 2020. THz Materials [online]. [viewed 10.07.2020]. Available from: http://www.tydexoptics.com/products/thz_optics/thz_materials/2. WHEELER, J. D., KOOPMAN, B., GALLARDO, P., MALONEY, P. R., BRUGGER, S., CORTES-MEDELLIN, G., DATTA, R., DOWELL, C. D., GLENN, J., GOLWALA, S., MCKENNE, C., MCMAHON, J. J., NIEMACK, M., PARSHLEY, S. and STACEY, G., 2014. Antireflection coatings for submillimeter silicon lenses. In: Millimeter, Submillimeter, and Far-Infrared Detectors and Instrumentation for Astronomy VII. Proceedings of SPIE. Vol. 9153. Bellingham, WA: Society of Photo-Optical Instrumentation Engineers (SPIE), id. 91532Z. DOI: https://doi.org/10.1117/12.20570113. KAPLUNOV, I. A., KOLESNIKOV, A. I., KROPOTOV, G. I. and ROGALIN, V. E., 2019. Optical Properties of Single-Crystal Germanium in the THz Range. Opt. Spectrosc. vol. 126, is. 3, pp. 191–194. DOI: https://doi.org/10.1134/S0030400X190300934. TYDEX, 2020. Synthetic Cristal Quartz. [online]. [viewed 10.07.2020]. Available from: http://www.tydexoptics.com/ materials1/for_transmission_optics/crystal_quartz/5. ZAIDEL, A. N., OSTROVSKAYA, G. V. and OSTROVSKY, YU. I., 1972. Spectroscopy Techniques and Practice. Moscow, Russia: Nauka Publ. (in Russian).6. EGOROV, V. N., 2007. Resonance methods for microwave studies of dielectrics (Review). Instrum. Exp. Tech. vol. 50, is. 2, pp. 143–175. DOI: https://doi.org/10.1134/S00204412070200177. KUZNETSOV, S. A., ASTAFEV, M. A., LAZORSKY, P. A., SKLYAROV, V. F., LONSHAKOV, YE. A. and ARZHANNIKOV, A. V., 2014. Spectral measurements of dielectric properties of polypropylene films in the subterahertz frequency range. Vestnik Novosibirskogo gosudarstvennogo universiteta. Seriya Fizika. vol. 9, is. 4, pp. 15–38. (in Russian).8. VLASOV, S. N., PARSHIN, V. V. and SEROV, E. A., 2010. Methods for investigating thin dielectric films in the millimeter range. Tech. Phys. vol. 55, is. 12, pp. 1781–1787. DOI: https://doi.org/10.1134/S10637842101201219. PARSHIN, V. V. and SEROV, E. A., 2015. Precise resonator methods investigation of dielectric and metal at 40 GHz – 500 GHz frequency range and in 4 K – 900 K temperature interval. Elektronika i Mikroelektronika SVCh. vol. 1, pp. 34–39. (in Russian). DOI: https://doi.org/10.1109/GSMM.2016.750031410. VALYANSKY, S. I., VINOGRADOV, S. V. and SAVRANSKY, V. V., 1992. Frequency-angle spectroscopy of surface plasmon polaritons excited in thin metal films. Pis’ma v Zhurnal Tekhnicheskoi Fiziki. vol. 18, is 5, pp. 70–73. (in Russian).11. GERASIMOV, V. V., KNYAZEV, B. A., NIKITIN, A. K. and ZHIZHIN, G. N., 2011. A way to determine the permittivity of metallized surfaces at terahertz frequencies. Appl. Phys. Lett. vol. 98, is. 17, id. 171912. DOI: https://doi.org/10.1063/1.358413012. AGRANOVICH, V. M. and MILLS, D. L., eds., 1985. Surface Polaritons: Electromagnetic Waves at Surfaces and Interfaces. Moscow, Russia: Nauka Publ. (in Russian).13. MAIER, S. A., 2007. Plasmonics: Fundamentals and Applications. New York: Springer US. DOI: https://doi.org/10.1007/0-387-37825-114. SPEVAK, I. S., TYMCHENKO, M. O., GAVRIKOV, V. K., KAMENEV, Y. Y., SHULGA, V. M., SUN, H.-B, FENG, J. and KATS, A. V., 2013. Influence of optical properties of a semiconductor and a periodic structure profile on the surface plasmon-polaritone resonance in the terahertz range. Radio Phys. Radio Astron. vol. 18, no. 4, pp. 341–348. (in Russian).15. KATS, A. V. and SPEVAK, I. S., 2002. Analytical theory of resonance diffraction and transformation of light polarization. Phys. Rev. B. vol. 65, is. 19, id. 195406. DOI: https://doi.org/10.1103/PhysRevB.65.19540616. SPEVAK, I. S., KUZMENKO, A. A., TYMCHENKO, M., GAVRIKOV, V. K., SHULGA, V. M., FENG, J., SUN H. B., KAMENEV, YU. E. and KATS, A. V., 2016. Surface plasmon-polariton resonance at diffraction of THz radiationon semiconductor gratings. Low Temp. Phys. vol. 42, is. 8, pp. 698–702. DOI: https://doi.org/10.1063/1.496049717. DZYBENKO, M. I. and RADIONOV, V. P., 2017. Laser method for measuring the refractive index of transparent substances in the terahertz range. Ukrainian Metrological Journal. no. 1, pp. 11–14. (in Russian). DOI: https://doi.org/10.24027/2306-7039.1.2017.101844